Theory of nuclear quadrupole interactions in solid hydrogen fluoride - Mohamed, Nor Sabirin; Sahoo, Narayan; Kelires, Pantelis C. (My University, 1990)
The nuclear quadrupole Interaction of 19F* (1=5/2) nucleus in solid hydrogen fluoride has been studied using the Hartree Fork Cluster technique to understand the Influence of both intrachaln hydrogen bonding effects and the weak Interchain Interaction. On the basis of our Investigations, the 34.04 MHz coupling constant observed by TDPAD measurements has been ascribed to the bulk solid while the observed 40.13 MHz coupling constant Is suggested as arising from a small two- or three- molecule cluster produced during the proton irradiation process. Two alternate explanations are offered for the origin of coupling constants close to 40 MHz in a number of solid hydrocarbons containlng hydrogen and fluorine llgands.
Keywords: Hydrogen fluoride; Solid hydrogen; Irradiation